CD30+ Anaplastic Enteropathy-Associated T-cell Lymphoma Mimicking Crohn's Disease. (28th October 2021) - Harbert, J L; Da Silva Lameira, F; Beversdorf, W; Bhalla, R; Rinker, E
Abstract: Introduction/Objective: Enteropathy-associated T-cell lymphoma (EATL) is an aggressive peripheral T-cell lymphoma with a very poor prognosis. It is not uncommon for patients with EATL to present with intestinal obstruction or perforation, with the diagnosis made following surgical resection or autopsy. Although EATL is associated with celiac disease, this diagnosis may be made concomitant with EATL. The symptomology is often non-specific, particularly without a known history of celiac disease, and progression may be rapid. Methods/Case Report: We describe the case of a 57 year old male who presented with several months of diarrhea, fatigue, night sweats, severe weight loss, and failure to thrive. Initial workup indicated positivity for Clostridium difficile and cryptosporidium, leading to antibiotic treatment. His symptoms persisted without significant improvement and a presumptive diagnosis of Crohn's disease was made based on colonoscopy with biopsy and imaging that showed inflammatory changes with entero-enteric fistula formation. Further clinical decline necessitated exploratory laparotomy which revealed multiple enteric strictures, intra-loop abscesses, and necrotic ulceration necessitating segmental ileal resections. There was no associated lymphadenopathy. Microscopically, there was a dense, polymorphic lymphoid population within the bowel wall with associated mucosal ulceration and abundant necrosis. Striking anaplastic cytomorphology was present, with a heavy intratumoral eosinophilic infiltrate. Neoplastic lymphocytes were CD3+, CD30+ T cells with a CD7+, CD5-, CD4-, CD8-, CD56-, ALK- immunophenotype. The adjacent intestinal mucosa showed features of celiac disease (villous atrophy, intraepithelial lymphocytosis). Results (if a Case Study enter NA): NA Conclusion: The prominent anaplastic morphology in combination with strong, diffuse CD30 expression prompted consideration of other T cell lymphomas, including anaplastic large cell lymphoma and peripheral T cell lymphoma, NOS, within the differential. The presence of coexisting histologic changes of celiac disease, dense eosinophilic infiltrate, and absence of lymphadenopathy were clues to the correct diagnosis. Notably, the frequency of CD30 expression in EATL is variable but common among cases manifesting large cell morphology.